The bvFTD phenocopy syndrome: a case study supported by repeated MRI, [18F]FDG-PET and pathological assessment. Issue 2 (4th March 2021) - van Engelen, Marie-Paule E.; Rozemuller, Annemieke J.M.; Ulugut Erkoyun, Hülya; Groot, Colin; Fieldhouse, Jay L.P.; Koene, Ted; Ossenkoppele, Rik; Gossink, Flora T.; Krudop, Welmoed A.; Vijverberg, Everard G.B.; Dols, Annemieke; Barkhof, Frederik; et al.
ABSTRACT: A clinical syndrome with neuropsychiatric features of bvFTD without neuroimaging abnormalities and a lack of decline is a phenocopy of bvFTD (phFTD). Growing evidence suggests that psychological, psychiatric and environmental factors underlie phFTD. We describe a patient diagnosed with bvFTD prior to the revision of the diagnostic guidelines of FTD. Repeated neuroimaging was normal and there was no FTD pathology at autopsy, rejecting the diagnosis. We hypothesize on etiological factors that on hindsight might have played a role. This case report contributes to the understanding of phFTD and adds to the sparse literature of the postmortem assessment of phFTD.